Hexagonal Barbell Deadlift One-repetition Maximum Estimation Using Velocity Recordings - Janicijevic, Danica; Senturk, Deniz; Akyildiz, Zeki; Gu, Yaodong; García-Ramos, Amador (International Journal of Sports Medicine, 2024)
This study aimed to determine whether the optimal minimal velocity threshold (MVT) provides more precise estimates of one-repetition maximum (1RM) in the hexagonal barbell deadlift (HBD) than the general and individual MVTs. The 1RMs of 27 resistance-trained males were predicted using three types of MVT: (i) General MVT: averaged across subjects’ velocity of the 1RM trial (0.25 m·s-1), (ii) individual MVT: velocity attained during the 1RM trial, and (iii) Optimal MVT: MVT that eliminated the differences between the actual and predicted 1RM. Two individual load-velocity relationships were modelled considering five (30-50-70-80%1RM) or six (30-50-70-80-90%1RM) loading conditions. Negligible differences (Effect size<0.20), low absolute errors (<5% of the actual 1RM), and extremely high correlations (r>0.90) were observed between the actual and six predicted 1RMs. The only significant difference was the lower raw errors for the 90%1RM condition (0.60±7.34 kg) compared to the 80%1RM condition (2.27±7.54 kg; p=0.013). These results suggest that the individual load-velocity relationship offers an accurate estimation of the HBD 1RM in resistance-trained males, and these estimates could maintain similar levels of precision across different types of MVT (general, individual, and optimal) and final tested loads (80%1RM and 90%1RM).
Keywords: muscle strength; resistance training; velocity-based training; weight lifting